RESEARCH AND ASSESSMENT OF THE NEED FOR NITROGEN FERTILIZERS OF THE EARLY MATURING RICE VARIETY “ALMAZ” DEPENDING ON THE PLANTING TIME - Zhalmenova Sapargul Bekniyazvona, (EPRA International Journal of Research and Development (IJRD), 2023)
The article discusses the study and assessment of the need for nitrogen fertilizers in the early ripening rice variety "Almaz" depending on the planting date. During the study, the agrophysical properties of the soil down to the groundwater level were studied, and the genetic layer of the soil was also studied. In an experiment conducted in a greenhouse, 3 different doses of mineral fertilizers were used for the Almaz rice variety.